Start-up, treatment performance and methane production of one-stage upflow anaerobic sludge blanket (UASB) reactor for fish processing wastewater - Villa, Benjamin C.
There is a current wastewater volume increase in seafood industry due to increasing demand worldwide. The generated wastes from these industries contained contaminants that are harmful to the environment. Hence, anaerobic treatment for this kind of wastewater is a must. One of the challenges in anaerobic treatment is the long start-up period while there were only few published studies on the effects of changing organic loading rates (OLRs) to fish processing wastewater treatment facilities. This study applied a different acclimatization strategy to accelerate and evaluate the treatment performance of microorganisms at high of contaminants at varying OLRs using a one-stage Upflow Anaerobic Sludge Blanket (UASB) reactor. The reactor was started up, operated subjected to two types of wastewater: (i) synthetic and (ii) fish processing. The reactor filled with seed sludge from a brewery plant in the Philippines was fed with wastewater at varying organic loading rates (OLRs) of 2.0, 3.1, 6.0, 3.0 and 4.5 g COD/l/d and was evaluated in terms of pH, ammonium-Nitrogen (NH4?-N), chemical oxygen demand (COD) removal and methane production. Maximum COD removal of 94.33 ± 4.85%, methane yield of 33.49%, protein degradation of 98.79% were achieved at organic loading rate (OLR) of 4.5 gCOD/l/d and influent COD level of 4,000-4,500 mg/L. The lowest effluent COD concentration achieved was 50 mg/l. At OLR of 3 g COD/l/d, the highest biogas production rate of 101.33 l/d was achieved.